Assessment of paravalvular regurgitation after transcatheter aortic valve replacement using 2D multi-velocity encoding and 4D flow cardiac magnetic resonance - Rooijakkers, Maxim J.P.; El Messaoudi, Saloua; Stens, Niels A.; Van Wely, Marleen H.; Habets, Jesse; Brink, Monique; Rodwell, Laura; Giese, Daniel; Van Der Geest, Rob J.; Van Royen, Niels; Nijveldt, Robin (European Heart Journal - Cardiovascular Imaging, 2024)
Aims: To compare the novel 2D multi-velocity encoding (venc) and 4D flow acquisitions with the standard 2D flow acquisition for the assessment of paravalvular regurgitation (PVR) after transcatheter aortic valve replacement (TAVR) using cardiac magnetic resonance (CMR)-derived regurgitant fraction (RF). Methods and results: In this prospective study, patients underwent CMR 1 month after TAVR for the assessment of PVR, for which 2D multi-venc and 4D flow were used, in addition to standard 2D flow. Scatterplots and Bland-Altman plots were used to assess correlation and visualize agreement between techniques. Reproducibility of measurements was assessed with intraclass correlation coefficients. The study included 21 patients (mean age ± SD 80 ± 5 years, 9 men). The mean RF was 11.7 ± 10.0% when standard 2D flow was used, 10.6 ± 7.0% when 2D multi-venc flow was used, and 9.6 ± 7.3% when 4D flow was used. There was a very strong correlation between the RFs assessed with 2D multi-venc and standard 2D flow (r = 0.88, P < 0.001), and a strong correlation between the RFs assessed with 4D flow and standard 2D flow (r = 0.74, P < 0.001). Bland-Altman plots revealed no substantial bias between the RFs (2D multi-venc: 1.3%; 4D flow: 0.3%). Intra-observer and inter-observer reproducibility for 2D multi-venc flow were 0.98 and 0.97, respectively, and 0.92 and 0.90 for 4D flow, respectively. Conclusion: Two-dimensional multi-venc and 4D flow produce an accurate quantification of PVR after TAVR. The fast acquisition of the 2D multi-venc sequence and the free-breathing acquisition with retrospective plane selection of the 4D flow sequence provide useful advantages in clinical practice, especially in the frail TAVR population.
CRIS-Team Scopus Importer:2024-07-19
Keywords: aortic stenosis; cardiac magnetic resonance; paravalvular regurgitation; transcatheter aortic valve replacement